Studi Gaya Desain Interior Restoran Bentoya di Galaxy Mall Surabaya - Dewi, Purnama (Intra, 2013)
Bentoya restaurant is one of the Japanese restaurants in Surabaya which adapted elements of Japanese culture on every element of the restaurants interior so that visitors who come can enjoy a cozy meal and at the same time feel a strong cultural atmosphere. But it would be better if all of Â the elements are not only beautiful but also has a meaning and a story to tell ascending. For that, this paper will reveal the meaning of existing interior elements in this restaurant by conducting field studies, interviews and literature then in comparison with the situation in the field and analyzed, so as to infer what the Japanese cultural meaning contained in the interior elements in this restaurant.